Corporate Social Responsibility: An Overview and New Research Directions: Thematic Issue on Corporate Social Responsibility [From the Editors] - WANG, Heli (Institutional Knowledge at Singapore Management University, 2016)
The idea of corporate social responsibility (CSR)—that is, businesses bearing a responsibility to society and a broader set of stakeholders beyond its shareholders—gained currency in the 1960s. Since then, attention on CSR has been growing in both academic and practitioner communities around the world. While there have been criticisms and debates on whether it was appropriate for corporations to expand their remit beyond shareholder value, an increasing majority of corporations have proactively committed to addressing larger societal challenges. With a variety of options for corporate engagement in mainstream society and local communities, corporations have created dedicated organizational units to effectively manage their social obligations. There is commensurate growth in specialized organizations operating at national and global levels that advise on, and often implement, targeted short-term projects or longer-term sustained community-level programs. Over 8,000 companies from more than 150 countries are signatories to the United Nations’ Global Compact, covering issues on human rights, labor standards, the environment, and anti-corruption initiatives. The scale and prominence of these trends indicate that discussions of CSR have shifted from existential questions regarding organizational mission and shareholder value to the mechanisms and processes by which corporations conceptualize and enact their societal obligations. Similarly, the dialog has shifted from simplistic justifications of financial outcomes related to core businesses to sophisticated views and measures of societal outcomes